Abscisic acid enhances tolerance of wheat seedlings to drought and regulates transcript levels of genes encoding ascorbate-glutathione biosynthesis - Liting, Wei; Lina, Wang; Yang, Yang; Pengfei, Wang; Tiancai, Guo; Guozhang, Kang (Frontiers in Plant Science, 2015)
Glutathione (GSH) and ascorbate (ASA) are associated with the abscisic acid (ABA)-induced abiotic tolerance in higher plant, however, its molecular mechanism remains obscure. In this study, exogenous application (10 μM) of ABA significantly increased the tolerance of seedlings of common wheat (Triticum aestivum L.) suffering from 5 days of 15% polyethylene glycol (PEG)-stimulated drought stress, as demonstrated by increased shoot lengths and shoot and root dry weights, while showing decreased contents of hydrogen peroxide (H2O2) and malondialdehyde (MDA). Under drought stress conditions, ABA markedly increased contents of GSH and ASA in both leaves and roots of ABA-treated plants. Temporal and spatial expression patterns of eight genes encoding ASA and GSH synthesis-related enzymes were measured using quantitative real-time reverse transcription polymerase chain reaction (qPCR). The results showed that ABA temporally regulated the transcript levels of genes encoding ASA-GSH cycle enzymes. Moreover, these genes exhibited differential expression patterns between the root and leaf organs of ABA-treated wheat seedlings during drought stress. These results implied that exogenous ABA increased the levels of GSH and ASA in drought-stressed wheat seedlings in time- and organ-specific manners. Moreover, the transcriptional profiles of ASA-GSH synthesis-related enzyme genes in the leaf tissue were compared between ABA- and salicylic acid (SA)-treated wheat seedlings under PEG-stimulated drought stress, suggesting that they increased the contents of ASA and GSH by differentially regulating expression levels of ASA-GSH synthesis enzyme genes. Our results increase our understanding of the molecular mechanism of ABA-induced drought tolerance in higher plants